Research on Safety Monitoring Management System of Earth-Rock Dams Based on BIM+GIS and Its Application - ZHANG Xiaoyang; HANG Xuchao; JIA Yuhao; QIAN Feng (Renmin Zhujiang)
Considering the problems such as difficult assets management and data barriers during the operation stage of hydropower engineering,the BIM+GIS technology is introduced to effectively integrate structured and unstructured data in every stage and facilitate the digitization of engineering and capitalization of data.Combined with this technology,a system for safety monitoring management is constructed,which is based on the whole life cycle management and driven by digital transformation. In addition,a three-dimensional (3D) design solution for earth-rock dams based on Bentley software is put forward to build a fine 3D model with unique codes connected to the whole process of instrument management.Thus,multi-source data are collected and integrated into this system to ensure system applications.The system functions mainly include visual displays,monitoring instrument management,as well as data management and analysis.The application of the system in earth-rock dams in Hubei Province shows good results,which has laid a solid foundation for the digital and intelligent operation and maintenance of engineering.